Teaching the Secrets of Folk Crafts Using Innovative Technologies (On the Example of Act and Smart Technology) - Baxromova Maftuna Sobirjon qizi (Zien Journals, 2022)
This article describes the use of innovative technologies in technology classes for students, the use of SMART technology in teaching folk crafts
Keywords: innovation; technology; educational technolog; innovative educational technology